Language Diversity in the USA / [electronic resource] - Potowski, Kim (Cambridge : Cambridge University Press, 2010)
What are the most widely spoken non-English languages in the USA? How did they reach the USA? Who speaks them, to whom, and for what purposes? What changes do these languages undergo as they come into contact with English? This book investigates the linguistic diversity of the USA by profiling the twelve most commonly used languages other than English. Each chapter paints a portrait of the history, current demographics, community characteristics, economic status, and language maintenance of each language group, and looks ahead to the future of each language. The book challenges myths about the 'official' language of the USA, explores the degree to which today's immigrants are learning English and assimilating into the mainstream, and discusses the relationship between linguistic diversity and national unity. Written in a coherent and structured style, Language Diversity in the USA is essential reading for advanced students and researchers in sociolinguistics, bilingualism, and education.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).